2019
DOI: 10.4314/rjmhs.v2i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Birth asphyxia at a district hospital in Kigali, Rwanda

Abstract: _________________________________________________________ AbstractBackground Prematurity, birth asphyxia (BA), and sepsis are the leading causes of neonatal mortality. The BA prevalence rate is 23% worldwide and affects up to 39% in Rwanda. Birth asphyxia is an insult with significant consequences to the neonate's brain and other vital organs due to decreased oxygen before, during or immediately after birth. Objective To assess the BA prevalence, associated factors, and outcomes at a district hospital in Kigal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…As far as our search, the pooled prevalence of birth asphyxia was not previously investigated in sub-Saharan Africa. The findings of previous studies on the magnitude of birth asphyxia were inconsistent and ranged from 3.1% [ 24 ] to 39.7% [ 27 ] across the sub-Saharan African countries. Hence, this systematic review and meta-analysis study was aimed at determining the pooled estimate prevalence of birth asphyxia and its association with gestational age, low birth weight, and parity among neonates in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…As far as our search, the pooled prevalence of birth asphyxia was not previously investigated in sub-Saharan Africa. The findings of previous studies on the magnitude of birth asphyxia were inconsistent and ranged from 3.1% [ 24 ] to 39.7% [ 27 ] across the sub-Saharan African countries. Hence, this systematic review and meta-analysis study was aimed at determining the pooled estimate prevalence of birth asphyxia and its association with gestational age, low birth weight, and parity among neonates in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Globally, birth asphyxia, preterm birth, birth defects, and infections caused the most neonatal deaths in 2017. [1] A recent retrospective study in Rwanda, by Uwingabire and Gowan, [5] found a 40% birth asphyxia rate among neonates admitted to the Neonatal Intensive Care Unit (NICU). A recent matched case-control study in Rwanda also found pneumonia and meningitis are common causes of neonatal mortality, with nearly a third dying at home.…”
mentioning
confidence: 99%
“…[1] According to the World Health Organization (WHO), about 10 million neonates do not breathe at birth, and six million require basic neonatal resuscitation (NR). [4] Basic NR, at time of birth, comprises of a set of interventions -beginning with drying and stimulation -that is required to establish breathing and circulation in a neonate who is not spontaneously breathing or crying. [4] Approximately 10% of all neonates require basic resuscitation at birth, [2] and less than 1% require advanced resuscitation and ongoing inpatient specialized care.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Basic NR, at time of birth, comprises of a set of interventions -beginning with drying and stimulation -that is required to establish breathing and circulation in a neonate who is not spontaneously breathing or crying. [4] Approximately 10% of all neonates require basic resuscitation at birth, [2] and less than 1% require advanced resuscitation and ongoing inpatient specialized care. [5] The strategy to reduce neonatal mortality is to improve the quality of basic NR at birth, which is estimated to reduce the mortality rate by 30% in lowresource settings with full-term neonates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation